240. Evaluation of 3D printing materials for breast phantoms for phase contrast imaging. (December 2018) - Esposito, G.; Mettivier, G.; Bliznakova, K.; Russo, P.; Di Lillo, F.; Sarno, A.; Bravin, A.; Buliev, I.; Popov, P.; Ivanov, D.
Abstract : Purpose: The aim of this work was to explore the available 3D printing technology and available range of printing materials such as resins, polylactic acid, nylon, ABS, etc. in order to determine their complex refractive index properties with respect to those of PMMA and of the breast tissues: adipose, glandular tissue and skin. Methods: Three step wedge phantoms were printed, each consisting of 3 steps with a rectangular area of 20 mm  × 35 mm for a total of 9 thicknesses ranging from 2 mm to 40 mm. Twenty stereolithographic plastic materials were investigated, including ABS, PLA, PVA, Nylon, Black, Hybrid and PET-G. We performed propagation based phase contrast projection imaging at ESRF (Grenoble, France), beamline ID17 at 30, 45 and 60 keV. Attenuation coefficients (derived from Lambert-Beer law) and refractive index decrements (derived using the Paganin phase retrieval algorithm) were derived in relative terms, with respect to propagation in an equivalent thickness of breast tissues. Results: The absolute difference in percent in terms of the attenuation coefficients and phase shift for different materials with respect to adipose tissue, glandular tissue, skin and PMMA, was measured respectively. Most materials show a difference of less than 5%. Conclusions: Twenty tissue substitute materials were considered as possible candidates to represent PMMA, adipose tissue, glandular tissue and skin. At 30 to 60 keV, the absolute percent difference between the glandular, adipose or skin and the substitute material was less than 5%. PVA material is the best representative for breast tissue and PMMA.